Stable oxygen isotopes - A new approach for tracing the origin of oxide inclusions in steels - Göbbels, Matthias; Pack, Andreas; Hoernes, Stephan; Bross, Rainer; Buhr, Andreas (European Journal of Mineralogy, 2005)
We introduce a new approach for tracing the origin submerged entry nozzle precipitates (clogging) in continuous casting processes using stable oxygen isotopes. The isotopic signatures of possible oxygen sources are compared with the isotope ratios in the precipitates. We use infra-red laser fluorination in combination with continuous flow gas mass spectroscopy to determine the oxygen ratios in the highly refractory, alumina-rich precipitates and possible oxygen sources. Our isotope data indicate that atmospheric oxygen is not the major source of oxide precipitates in the submerged entry nozzles. Also process oxygen from the converter can be excluded to be source of oxygen in clogging. A possible origin of oxygen in alumina-rich precipitates from olivine from refractory material is discussed. © 2005 E. Schweizerbart'sche Verlagsbuchhandlun
UnivIS-Import:2015-03-09:Pub.2005.nat.dgeo.IGM.LM.stable
Keywords: Continuous casting; Non-metallic inclusions; Oxygen isotopes